Yesterday's war; tomorrow's technology: peer commentary on ‘Ethical, legal, social and policy issues in the use of genomic technologies by the US military’ - Evans, Nicholas G. (J Law Biosci, 2014)
A recent article by Maxwell J. Mehlman and Tracy Yeheng Li, in the Journal of Law and the Biosciences, sought to examine the ethical, legal, social, and policy issues associated with the use of genetic screening and germ-line therapies (‘genomic technologies’) by the US Military. In this commentary, we will elaborate several related matters: the relationship between genetic and non-genetic screening methods, the history of selection processes and force strength, and the consequences and ethics of, as Mehlman and Li suggest, engineering enhanced soldiers. We contend, first, that the strengths of genomic testing as a method of determining enrollment in the armed forces has limited appeal, given the state of current selection methods in the US armed forces. Second, that the vagaries of genetic selection, much like other forms of selection that do not bear causally or reliably on soldier performance (such as race, gender, and sexuality), pose a systematic threat to force strength by limiting the (valuable) diversity of combat units. Third, that the idea of enhancing warfighters through germ-line interventions poses serious ethical issues in terms of the control and ownership of ‘enhancements’ when members separate from service.